Does Anterior Commissure Involvement Change the Selection of Treatment Modality in Early-Stage Glottic Larynx Cancer? - Aliyeva, Chinara; Dağdelen, Meltem; Yener, Haydar Murat; Hekim, Muhammed Veysel; Şahin, Merve; Tevetoğlu, Fırat; Peker, Sinem Kara; Yılmaz, Yetkin Zeki; Gözen, Emine Deniz; Karaman, Emin; Can, Günay; Uzel, Ömer Erol (Cerrahpaşa Medical Journal, 2023)
Objective: Glottic laryngeal cancers are detected at an early stage at the time of diagnosis. Radiotherapy or transoral laser microsurgery as a local treatment is a choice for early-stage glottic laryngeal cancer. This study aims to investigate the local control rate after radiotherapy or transoral laser microsurgery for early-stage glottic laryngeal cancer with anterior commissure involvement. Methods: In total, 119 patients with early-stage (Tis-T1-2) laryngeal cancer were treated in our institution with radiotherapy or transoral laser microsurgery between 2009 and 2021. The median follow-up time was 52 months. Seventy-three patients underwent transoral laser microsurgery. Forty-six patients received radiotherapy, and there were 41 patients with anterior commissure involvement. Results: The 2 and 5 years overall survival rates were 92% and 73%, whereas local failure-free survival rates were 84% and 82% in all groups, respectively. The 2-year overall survival was 88% in the radiotherapy arm and 94% in the transoral laser microsurgery arm, respectively. There was no statistically significant difference between the two treatment groups for overall survival (P: .062). According to anterior commissure involvement, 29 underwent transoral laser microsurgery, whereas 12 patients received radiotherapy. A total of 9 local failures occurred in the transoral laser microsurgery group, there was no recurrence in the radiotherapy group (P: 0.028). Conclusion: There was no statistically significant difference between the two treatment groups for local failure-free survival and overall survival. However, in the case of the anterior commissure involvement, 9 local failures occurred in the transoral laser microsurgery group, and there was no recurrence in the radiotherapy group. Radiotherapy might be recommended in early-stage glottic laryngeal cancer, especially in patients with anterior commissure involvement. Cite this article as: Dağdelen M, Yener HM, Hekim MV, et al. Does anterior commissure involvement change the selection of treatment modality in early-stage glottic larynx cancer? Cerrahpaşa Med J. 2023;47(3):285-290.